New Public Management Reforms and Hospitals Accreditation Process in Portuguese NHS - Picoito, C.; Major, M. (TMQ - Techniques, Methodologies and Quality, 2013)
This study is part of a PhD thesis where we intend to investigate the pressures that are under hospital accreditation processes and how it changed those organizations. In the last decade Portuguese public hospitals were corporatized (Barros et al., 2011) and many public hospitals embarked on Accreditation process as a mean of searching for higher services quality. Drawing on institutional theory, DiMaggio and Powell [4] and Scott [12], this study seeks to analyze the reasons behind accreditation process and the pressures posed by external and global entities, namely the EU and the European Foundation for Quality Management (EFQM), in this process. To this end an intensive and longitudinal case study is being carried out in a specific hospital located in Setúbal (Hospital of Outão). This paper is organized as follows: in section 1 we present the reasons that leaded to the emergence of the NPM movement and in section 2 we explain the reasons why we chose institutional theory to “frame the work”. In section 3 we state why a case study strategy was followed and the relevance of a local vs global analysis. The paper ends with the presentation of preliminary findings